Frictional Healing Measurements on SAFOD Samples - Matt J Ikari (PANGAEA, 2020)
We conducted laboratory friction experiments measuring time-dependent frictional strengthening (healing) on fault zone and wall rock samples recovered during drilling at the San Andreas Fault Observatory at Depth (SAFOD), located near the southern edge of the creeping section and in the direct vicinity of three repeating microearthquake clusters. Samples are from two actively creeping fault strands, termed the Central Deforming Zone (CDZ) and the Southwest Deforming Zone (SDZ). For all samples, mineralogic composition was quantified by X-Ray Diffraction (XRD), including clay mineral species. For shearing tests, all samples were crushed and sieved to a grain size < 125 μm. Samples were mixed with distilled water and sheared in a modified Wykeham-Farrance Bromhead ring shear apparatus, under a constant normal load of 1 MPa and controlled temperature of 20 °C. We conducted slide-hold-slide tests, during which the driving velocity is held at zero for a prescribed amount of time (t) before shearing is resumed at 10 μm/s. The hold time is increased in half-order of magnitudes (approximately 3-fold) in the range of 10 to ~350,000 seconds, with at least 1 mm of shearing in between holds.